Is Tax Competition Strategic? Spatial Distributions of Business Property Tax Abatements in the Chicago Suburbs. Issue 1 (February 2021) - Funderburg, Richard; Drucker, Joshua; Merriman, David; Weber, Rachel
The authors analyze the locations of property tax abatements awarded to businesses in Cook County, Illinois from 2012 to 2014 to explore their spatial distribution and to examine local government motivations for awarding incentives. The authors' analysis, which controls for the spatial distribution of businesses, reveals a clustering of abatements at intramunicipal geographic scales. They also find amplified probabilities that abatements are awarded to businesses located near tax increment financing districts or enterprise zones. These patterns suggest that local governments use abatements in a strategic fashion to advance policy goals. The authors use the same data to develop three indices of the degree of abatement clustering at the municipal scale for each of the 64 municipalities in Cook County that awarded five or more abatements. Most of the Chicago suburbs exhibit a pattern consistent with the strategic award of business tax incentives.